2016
DOI: 10.1002/adem.201600617
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Transparent Scratch Resistant Coating through Direct Oxidation of Al‐Coated Glass

Abstract: The authors develop a protective transparent coating of aluminum oxide through direct oxidation of aluminum-coated glass. Aluminum coatings are deposited on low-iron glass substrates using a physical deposition method and then oxidized at different temperatures. A uniform nano-porous structure with grain sizes of approximately 30-80 nm is observed. X-ray diffraction, TEM images, and EDX analysis indicate the formation of crystalline g-Al 2 O 3 , Si, and stishovite-SiO 2 as a result of interdiffusion. The sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Some coatings promote diffuse light fraction or block some wavelengths of light (e.g. aluminum coating (Mousavi et al 2017) and Smart Glass film (Chavan et al 2020). Moreover, Huh et al (2018) reported a moth-eye structure pattern that can be directly printed on the film, protective glass or solar panels that allows mechanical robustness and anti-reflection.…”
Section: Developing Innovative Cover Materials For Protected Croppingmentioning
confidence: 99%
See 1 more Smart Citation
“…Some coatings promote diffuse light fraction or block some wavelengths of light (e.g. aluminum coating (Mousavi et al 2017) and Smart Glass film (Chavan et al 2020). Moreover, Huh et al (2018) reported a moth-eye structure pattern that can be directly printed on the film, protective glass or solar panels that allows mechanical robustness and anti-reflection.…”
Section: Developing Innovative Cover Materials For Protected Croppingmentioning
confidence: 99%
“…Air-inflated polyethylene film (DPE) and twin-wall polycarbonate sheet (DPC) are investigated the increase of 70% and 100% diffused light, respectively (Hao et al 2016). Aluminum coating with scratch-resistance deposits in low iron glass resulted in the transmission of 75-85% visible wavelengths (Mousavi et al 2017). Recently, Chavan et al (2020) (Fig.…”
Section: Greenhouse Light Condition Modified By Advanced Cover Materialsmentioning
confidence: 99%
“…[ 4,5 ] With the purpose of application in several particular fields, such as optical coatings and protective coating for interior decoration surface materials, including natural stone, artificial stone, and glass…., the NCTFs need to meet the requirements such as high transmittance in the visible region (greater than 85% in the wavelength range from 400 to 800 nm), strong absorption in the UV region (250–380 nm), high hardness, excellent anti‐scratch, and abrasive resistance. [ 6,7 ]…”
Section: Introductionmentioning
confidence: 99%
“…Variations in coating thickness and morphology, surface roughness, primary particles size and surface wetting issues are still problematic for sol-gel based methods for inorganic and hybrid coatings [8]. Solventless processes such as Physical Vapor Deposition (PVD) and Chemical Vapor Deposition (CVD) do not suffer from surface wetting issues and reproducibly synthesize high quality conformal thin film coatings over complex substrate geometries [9]. Precise thickness control and excellent coating uniformity are main advantages of PVD and CVD fabricated coatings.…”
Section: Introductionmentioning
confidence: 99%
“…Precise thickness control and excellent coating uniformity are main advantages of PVD and CVD fabricated coatings. Titanium nitride, zirconium nitride, silicon nitride, sapphire, calcite, barium fluoride, calcium fluoride, quartz, lithium fluoride, diamond like carbon coatings and other inorganic oxides are widely used as protective coating materials [9,10]. However, PVD and CVD methods are usually associated with elevated temperatures and highly energetic deposition environments hindering the applicability due to substrate material limitations.…”
Section: Introductionmentioning
confidence: 99%